Visionary leadership: the mediating role of organizational support on nurse interns’ creativity and organizational effectiveness - Manal Saleh Moustafa Saleh; Aisha Elsayed-El Araby Abdelwahid; Hanan Elsaid Elsabahy; Ashraf Amin Eltahan; Azza Abdeldayem Ata (BMC Nursing)
Abstract Aim This study examines the influence of visionary leadership on nurse interns’ creativity and organizational effectiveness, with a particular focus on the mediating role of perceived organizational support. Background Leadership, particularly in healthcare care, significantly influences employee experiences and outcomes. Visionary leaders support their employees to gain organizational commitment and improve their creativity. However, the impact of visionary leaders on creativity among nurses and organizational effectiveness requires further exploration. Organizational support plays a crucial mediating role in the relationship between visionary leadership and nurses’ creativity. When nurses perceive strong organizational support, they feel more valued and are more likely to engage in creative behaviors. Subjects and methods A descriptive correlational design was conducted among nurse interns in Mansoura University Hospitals, Egypt. Four standardized questionnaires were used to examine perceptions of visionary leadership, organizational support, creativity among nurse interns, and organizational effectiveness perception; 464 nurse interns were polled. The study’s hypothetical model was examined using AMOS structural equation modeling (SEM). Results Visionary leadership perception significantly affects nurse interns’ creativity, organizational effectiveness, and perceived organizational support. As well, nurse interns’ creativity significantly affects organizational effectiveness. Moreover, perceived organizational support mediates the relationship between visionary leadership as regards nurse interns’ creativity and organizational effectiveness, Conclusions In sum, fostering a supportive environment and employing visionary leadership can empower nurse interns to be more creative, leading to enhanced problem-solving, improved processes, and better overall performance within healthcare organizations. This emphasizes the importance of leadership and support in driving innovation and effectiveness in healthcare settings. Clinical trial number Not applicable.